Address to the U.N. Economic and Social Council, United Nations, NY, December 5, 1968 - McNamara, Robert S. (2016)
These are the prepared remarks of Robert S. McNamara, President of the World Bank, International Finance Corporation, and the International Development Association (IDA). He declares that our common enterprise is to drive back poverty, to lift living standards and to enhance the dignity of man. The Bank intends to lend twice as much in the next five years as in the previous five. He discusses the Bank’s lending in Asia. He discusses new geographical accents. The Bank and IDA are now ready to finance state-owned development banks; and training of managers and agriculturalists. He discusses putting population policy at the center of future strategy.